Development of the Medical Record File Folder Design in Medical Record Unit RSUD dr. H. Slamet Martodirdjo, Pamekasan city - M.Afif Rijal Husni (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 1970)
All records of the patient's history of health service activities in the medical record file must be documented in a map or medical record document that can be a safeguard from loss, data leakage, data exchange, or damage. Fulfillment of needs and planning for the use of a medical record map is very important in documentation, because the planning of fulfilling the needs of the medical record map is expected to produce a good map design so that it can support the patient's clinical documentation quality. The type of this research is descriptive analytic qualitative research with the subject of research in the form of filing officers and heads of medical record units and research objects in the form of medical record file folders. Data analysis using descriptive analysis. The results showed that the medical record file folder in the RSUD Dr. RSUD dr. H. Slamet Martodirdjo Pamekasan Regency needs to develop the design because the medical record map currently used tends to have slippery material so that the map falls easily if it is arranged in a storage rack and the use of material is too thick so that it takes up a lot of space when stored on the medical record rack by observing aspects physical and content aspects.